2013
DOI: 10.1111/jfbc.12039
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Content, Antioxidant and Antimicrobial Activities of Two Fruit Varieties of Algerian Ficus carica L

Abstract: The present study deals with the evaluation of the in vitro antioxidant and antimicrobial potential of four different extracts of two varieties (Azendjar and Taamriout) of dried figs (Ficus carica L.) by using the 2,2-diphenyl-2-picrylhydrazyl radical and agar diffusion methods and minimum inhibitory concentration (MIC)-determination. Moreover, the extracts were investigated for their polyphenolic, flavonoidal and tannin content by using the Folin-Ciocalteu assay, the aluminium trichloride method and precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
2
29
0
3
Order By: Relevance
“…In recent study, the total phenolic content in dried fig fruits was analyzed using an oxidation–reduction colorimetric assay (Folin–Ciocalteu reagent) (Debib et al . ) which showed that dark fig fruits were richer in polyphenols than the green varieties. The flavonoid composition of the peel and pulp of two Italian fresh fig cultivars ( F. carica ) were analyzed by Del Caro and Piga (), using the HPLC–DAD method.…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, the total phenolic content in dried fig fruits was analyzed using an oxidation–reduction colorimetric assay (Folin–Ciocalteu reagent) (Debib et al . ) which showed that dark fig fruits were richer in polyphenols than the green varieties. The flavonoid composition of the peel and pulp of two Italian fresh fig cultivars ( F. carica ) were analyzed by Del Caro and Piga (), using the HPLC–DAD method.…”
Section: Discussionmentioning
confidence: 99%
“…9 Due to the presence of phenolic acids such as chlorogenic acid, quercetin-3-0-rutinoside (peels), and psoralen (pulp), Ficus fruits are utilized for the treatment of skin depigmentation. 24 Yang et al 25 reported that the methanolic extract of F. carica fruit showed the IC 50 value of 80.0 μg/mL, whereas the water extract of fruit showed the IC 50 value of 720.0 μg/mL in the DPPH model. Similarly, the water extract of the fruit also showed a moderate superoxide radical scavenging activity with the IC 50 value of 950.0 μg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…These herbals were based on ancient Greek authors, especially Dioscorides ( De Materia Medica , BC 78–77) and Galen, as also on references of Hippocrates ( Corpus Hippocratium: On Ancient Medicine, On Aliment or Nutriment , BC 460–377) appreciating fig as a phytonutrient. Its medicinal benefits include metabolic, cardiovascular, antispasmodic, antiviral, antioxidant, antibacterial and anti‐inflammatory remedies, as also potential anticancer activity …”
Section: Introductionmentioning
confidence: 99%